Influences on myocardial perfusion in non-obstructive coronary disease: an observational quantitative perfusion mapping study. (8th February 2021) - Knott, K; Seraphim, A; Augusto, JB; Camaioni, C; Kotecha, T; Xue, H; Joy, G; Bhuva, AN; Manisty, C; Brown, LAE; Wong, J; Fontana, M; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): This study was supported by a Clinical Training Research Fellowship (K. Knott) from the British Heart Foundation and directly and indirectly from the Biomedical Research Centre at University College London Hospitals and Barts Heart Centre. Background: Cardiovascular magnetic resonance (CMR) with automated inline perfusion mapping permits rapid fully automated non-invasive myocardial blood flow (MBF, ml/g/min). Understanding the microvascular component of MBF would help optimize epicardial coronary artery disease detection and potentially serve as an independent diagnostic / therapeutic target.  Purpose: To explore MBF influences at stress and rest in patients with unobstructed epicardial coronary arteries. Methods: 242 participants (mean age 56.9 years) from 5 European centers with unobstructed epicardial coronary arteries and no myocardial scar underwent adenosine vasodilator perfusion mapping at stress and rest. The factors influencing MBF were determined using univariate and multivariate linear regression analyses. Results: Mean rest perfusion was 0.91+/-0.24ml/g/min. Rest perfusion was higher in females (0.97+/-0.22ml/g/min vs 0.83 +/- 0.24ml/g/min) and lower in patients on beta blockers. Mean stress MBF was 2.53+/-0.82ml/g/min. Factors independently associated with reduced stress MBF were increasing age, diabetes, increasing left ventricular mass (LVMi) and the use of beta blockers.  The predicted stress MBF can be obtained from the equation MBF = 2.66–0.015(age-60)–0.013(LVMi-57)-0.405(diabetes)–0.365(beta blocker). This means stress MBF falls 10% over 19 years and that diabetes drops the MBF by the equivalent of being 27 years older. These changes are large: for example, a 70-year-old diabetic would have 30% lower stress MBF than a 35 year-old non-diabetic.  Conclusions: In the absence of obstructive epicardial coronary disease, stress MBF falls with age, diabetes, increased LV mass and beta-blockers. These data may help develop normal reference ranges, input to other modelling (eg CT FFR), and they advance perfusion mapping as a measure of microvascular function.